Button battery lodged in Meckel's diverticulum - Benjamin A. Farber; Eliana Shaul; Michael J. LaQuaglia; Elizabeth Janofsky; Mindy B. Statter; Dominique M. Jan; Steven H. Borenstein; Bryan Rudolph (Elsevier, 2018)
Meckel's diverticulum is the most common congenital anomaly of the gastrointestinal tract. It is relatively uncommon, however, for patients to become symptomatic and rarer still for foreign bodies to become lodged within a Meckel's diverticulum. Here we present one such case in which a button battery was lodged in a Meckel's diverticulum, along with the patient's subsequent interdisciplinary management and review of the relevant literature. Keywords: Foreign body ingestion, Button battery, Meckel's diverticulum